Radiometric Degradation Associated with Terrain Height Variations and Pulse Duration in Scan-On-Receive SAR Images - Bordoni, Federica; Krieger, Gerhard; Lind, David (IEEE Transactions on Geoscience and Remote Sensing, 2022)
Scan-on-receive (SCORE) is a key digital beamforming (DBF) technique for future high-resolution wide-swath spaceborne synthetic aperture radar (SAR) systems. Compared to a conventional approach, it allows improving the signal-to-noise ratio and the range ambiguity suppression. Nevertheless, it also exposes the system to new errors, associated with terrain height variations and pulse duration. This work investigates the mutual effect of these error sources on the SCORE SAR image. A novel, closed, a mathematical expression is derived, respectively, for the impulse response function of the image formation process and for the radiometric loss affecting the image pixels. This makes it possible to predict and quantify the effect of terrain height variations and pulse duration as a function of the system, processing, and geometric parameters. The numerical results, based on the end-to-end simulation of the SAR image formation process in different operational scenarios, highlight the relevance of this effect and the derived analytical description, especially in view of the demanding radiometric quality requirements imposed on future SAR images.
Created from Fastlane, Scopus look-up
Keywords: Elevation digital beamforming (DBF); high-resolution wide-swath (HRWS); multichannel synthetic aperture radar (SAR); scan-on-receive (SCORE)